Labour Employment in Paddy, Wheat and Vegetables in Kathmandu Valley, Nepal - Thapa, Prahlad Kumar (1986)
Unemployment and under-employment are major problems in Nepal resulting from growth in agricultural labour, insufficient agricultural land, small farm size and low cropping intensity. One way to alleviate such problems would be to adopts more intensive system of agriculture. This requires a knowledge on the labour absorption capacities of different crops. This study examines the employment of farm labour in vegetable cultivation as compared to cereal cultivation in Kathmandu valley. More specifically, it examines the influence of production function variables, cropping intensity and price of labour on the employment of total labour and, employment of family and hired labour separately in paddy, wheat and vegetable cultivation. The employment of total labour is modelled using a single equation model and the employment of family and hired labour is modelled using a simultaneous equation system. The total labour model is estimated by ordinary least squares technique and the simultaneous equation model is estimated by the instrumental variable estimation procedure. Variables such as farm size, tractor use, bullock power and price of labour are found significantly and negatively related to the employment of farm labour. The other set of variables such as seed-manure-fertilizer-pesticide, irrigation, high yielding varieties and cropping intensity are found significantly and positively related to the employment of farm labour. In addition, vegetable cultivation is found more profitable and more labour intensive than cereal cultivation. Vegetable cultivation is recommended as a possible solution to ease the problems of unemployment and under-employment in Nepal. Hired labour is found to be an important beneficiary of vegetable cultivation. Vegetable cultivation would therefore provide more employment opportunities to the landless and marginal farm workers in Nepal.